Control of hyperparathyroidism with the intravenous calcimimetic etelcalcetide in dialysis patients adherent and non-adherent to oral calcimimetics - Arenas, Maria Dolores (Clin Kidney J, 2020)
BACKGROUND: In dialysis patients, non-adherence to oral cinacalcet adds complexity to the control of secondary hyperparathyroidism. The present study aims to evaluate the use of intravenous calcimimetic, etelcalcetide, in the control of secondary hyperparathyroidism in patients adherent and non-adherent to oral calcimimetics. METHOD: The Simplified Medication Adherence Questionnaire was used to identify non-adherence. Almost half of the patients were non-adherent to the treatment with cinacalcet. Twenty-five patients (15 non-adherent) were switched from cinacalcet to etelcalcetide and were followed-up monthly for 8 months. RESULTS: Cinacalcet was discontinued for 1 week before the initiation of etelcalcetide. After this period, the serum PTH levels increased by2-fold in adherent patients, whereas it did not change in non-adherent patients suggesting that they were not taking the medication. Etelcalcetide progressively reduced serum parathyroid hormone (PTH) (mean ± standard deviation) from 818 ± 395 to 367 ± 289 pg/mL (P < 0.001) in non-adherents, and from 496 ± 172 to 228 ± 111 pg/mL (P < 0.01) in adherent patients with a mean dose of 7.0 ± 2.3 and 5.1 ± 1.2 mg in non-adherent and in adherent patients, respectively. Etelcalcetide increased the percentage of patients with PTH on target from 28% to 58%. Patients with serum calcium <8.4 mg/dL increased from 8% to 40%, although they remained asymptomatic. The percent of patients with serum phosphate on target increased from 40% to 65%. CONCLUSION: The lack of adherence to cinacalcet is a possible cause of the apparent lack of response to oral calcimimetic. The use of etelcalcetide ensures compliance and control of secondary hyperparathyroidism in both non-adherent and adherent patients.